Sistem Pendukung Keputusan Pemilihan Lokasi Sampel Dalam Blok Sensus Pada Survei Angkatan Kerja Nasional Dengan Menggunakan Metode Fuzzy Logic - Khoiruddin Siregar; Pristiwanto Pristiwanto; A.M Hatuaon Sihite (Bulletin of Information System Research, 2023)
The national labor force survey is a survey designed to get a general picture of employment and also to understand whether there have been changes in the structure of the workforce between enumeration periods. In this survey, not all census block areas were included in the enumeration and also not all families in the survey area were selected as the enumeration sites. So, for each selected region and household, it is hoped that it will be able to provide employment data based on education, working hours, industry classification and employment status as well as unemployment rates based on different characteristics and efforts to find work as well as the working age population that is not in the labor force. For this reason, to make efficient and effective decisions, here the author will use the fuzzy logic method because this method is very flexible where this method is able to adapt to changes and uncertainties, also has tolerance for imprecise data and can cooperate with control techniques. conventionally. The purpose of this study is to be able to make decisions about areas that are able to provide the information data needed in the labor force survey at BPS Padang Lawas Utara.